The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.jeurceramsoc.2014.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Thickness-dependence of the breakdown strength: Analysis of the dielectric and mechanical failure

Abstract: The breakdown strength as well as the mechanical strength of ceramic materials decreases with increasing volume. The volume-effect of the mechanical strength can be explained by the Weibull theory. For the breakdown strength the same explanation has been often assumed.In order to validate this assumption breakdown strength and mechanical strength of alumina samples with defined porosities were compared. Differences in the Weibull moduli of breakdown and mechanical strength distributions indicate that the volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(36 citation statements)
references
References 41 publications
1
27
3
1
Order By: Relevance
“…This is already a relative difference of 20.2% related to the large value, and 25.3% related to the small value, respectively. As described in the introduction, dielectric strength is indirectly proportional to the square root of the sample thickness [6,8]. Based on this relationship, a normalized dielectric strength E d,n with respect to a normalized thickness t n can be calculated according to Eq.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is already a relative difference of 20.2% related to the large value, and 25.3% related to the small value, respectively. As described in the introduction, dielectric strength is indirectly proportional to the square root of the sample thickness [6,8]. Based on this relationship, a normalized dielectric strength E d,n with respect to a normalized thickness t n can be calculated according to Eq.…”
Section: Discussionmentioning
confidence: 99%
“…A noteworthy characteristic of dielectric strength, especially with respect to test conditions, is its thickness dependence. In contrast to common mechanical strength concepts, dielectric strength shows a 1/ d dependence, where d is the sample thickness [6,8,15]. Neusel and Schneider [15] concluded that the thickness dependence cannot be explained by the Weibull concept.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Non-pottable and/or non-polymeric insulation materials, such as mica, ceramic (e.g., AlN and AlSiC), aramid (e.g., Nomex), polyimide (e.g., Kapton) also feature interesting properties, i.e. high breakdown strength (especially for thin layers), good resistance to partial discharges, and low losses [43], [62]. These materials are typically combined with potted polymeric materials or oils, in order to avoid the presence of air near the electric field hot spots, which can lead to partial discharges [56].…”
Section: Design Guidelinesmentioning
confidence: 99%
“…33 For thin films, the breakdown process can be described by an intrinsic, electric breakdown model originally proposed by von Hippel. [34][35][36] Bulk samples show a dependence of the breakdown strength on the sample thickness, 33,[37][38][39] which cannot be explained by the intrinsic, electric breakdown model. Different breakdown mechanisms of bulk samples and thin films might also be associated with different conduction mechanisms.…”
Section: Introductionmentioning
confidence: 99%